PERPADUAN IDENTITAS LOKAL DAN GLOBAL PADA DESAIN PASAR KULINER BENDUNGAN HILIR - Sutandi, Isabel Gloria Permatasari; Mustaram, Agnatasya Listianti (Jurusan Arsitektur dan Perencanaan, 2024)
Globalization, commercialization and mass communication have brought cultural and geographical homogenization into urban space, giving rise to the term placeless place, namely the reduction of the unique characteristics and identity of a place. One of the places experiencing this phenomenon is the market and Bendungan Hilir Area. Bendungan Hilir Market, which was founded in 1972, used to have the meaning of a